Wymuszanie wykonania obowiązków administracyjno-prawnych w wybranych krajach europejskich - Klat-Wertelecka, Lidia (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
Obligations under administrative law comprise those injunctions that result from binding decisions of public administration bodies or directly from the provisions of administrative law. Such concepts as legal obligation, sanction and constraint remain inextricably linked. In order for administrative acts to be effective, they must contain sanctions. The structure of a sanction implies an alternative: if an obligation is fulfilled, there is no sanction; if there is a failure to fulfil the obligation — the sanction is applied. In various European countries the fulfilment of obligations under administrative law is guaranteed by various means forms of enforcement. These include enforcement sanction, penal sanction and administrative penalty. In the case of a failure to fulfil a specific administrative obligation, some forms of enforcement may be used simultaneously and parallel to each other. European countries use various means to enforce administrative obligations. We can distinguish two basic models: a legal system in which public administration bodies are authorised to use means of enforcement, and a legal system without the classic institution of administrative enforcement. The first group of countries in which public administration bodies use administrative enforcement include Poland, Germany, Austria, the Czech Republic, Slovakia and Spain. Countries with a mixed system of administrative sanctions, without a clear administrative enforcement include Russia and the United Kingdom.
Keywords: środki przymusu państwowego; wymuszanie; obowiązki administracyjnoprawne w Niemczech; obowiązki administracyjnoprawne w Słowacji; obowiązki administracyjnoprawne w Rosji